Reseña de: Mitchell, Silvia Z., Queen, Mother, and Stateswoman: Mariana of Austria and the Government of Spain - Arroyo Vozmediano, Julio (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2020)
Reseña de: Mitchell, Silvia Z., Queen, Mother, and Stateswoman: Mariana of Austria and the Government of Spain. University Park, The Pennsylvania State University Press, 2019. xv + 293 pp. ISBN: 978-0-271-08339-1